Uji kualitas telur ayam ras terhadap lamanya penyimpanan berdasarkan sifat listrik (Quality test of eggs on the length of storage based on electrical properties) - Dela Prawita Mulza; - Ratnawulan; - Gusnedi (PILLAR OF PHYSICS, 2013)
ABSTRACT Many people like eggs because the price is cheap eggs also have high nutritional value, but not many know the influence of duration of storage on the quality of eggs. The purpose of this study was to determine the value of capacitance and electrical conductivity of the white and yellow eggs are stored in the refrigerator and the room is open for 30 days. Measurement of capacitance using a parallel plate capacitor chip connected to the LCR meter using a frequency of 1 KHz, 2 KHz, 3 KHz, 4 KHz and 5 KHz, while the value of measuring the electrical conductivity of the white and the yolk are used konduktivity meters. The results obtained that the duration of the storage effect on the quality of eggs. Capacitance values of the white and the yolk are stored impaired during storage, as well as the capacitance value for the eggs stored in the refrigerator, but do not drop too much and tend to be stable, the frequency affects the capacitance value the lower the frequency the greater the capacitance value obtained . Value conductivity values also decreased during storage, the decline is evident in storage 26 days to 30 days, the eggs conductivity values stored in the refrigerator also decreased but the values obtained stable.Keywords: eggs, white and yellow eggs, capacitance, conductivity.